(untitled) - Carson, Rachel (Boston, 2002)
First published by Houghton Mifflin in 1962, 'Silent Spring' alerted a large audience to the environmental and human dangers of indiscriminate use of pesticides, spurring revolutionary changes in the laws affecting our air, land, and water. 'Silent Spring' became a runaway bestseller, with international reverberations ... [It is] well crafted, fearless and succinct ... Even if she had not inspired a generation of activists, Carson would prevail as one of the greatest nature writers in American letters. This fortieth anniversary edition celebrates Rachel Carson's watershed book with a new introduction by the acclaimed Rachel Carson biographer Linda Lear, who tells the story of Carson's courageous defense of her truths in the face of ruthless assault from the chemical industry in the year following the publication of 'Silent Spring' and before her untimely death in 1964, and a new afterword by Edward O. Wilson.
Keywords: Thuốc trừ sâu,Pesticides; Khía cạnh môi trường,Environmental aspects